Serodiagnosis of Toxocariasis by ELISA Using Crude Antigen of Toxocara canis Larvae - Jin, Yan (The Korean Society for Parasitology and Tropical Medicine, 2013)
Toxocariasis is a worldwide zoonosis caused by larvae of ascarid nematodes of dogs or cats, Toxocara canis or T. cati. Diagnosis of human toxocariasis currently relies on serology that uses T. canis excretory-secretory antigen to detect specific IgG antibodies by ELISA. We investigated the serodiagnostic efficacy of ELISA using crude antigen of T. canis larvae (TCLA). Serum specimens of 64 clinically confirmed toxocariasis, 115 healthy controls, and 119 other tissue-invading helminthiases were screened by ELISA using TCLA. The ELISA using TCLA showed 92.2% (59/64 patient samples) sensitivity and 86.6% (103/119) specificity. Its positive diagnostic predictivity was 78.7% and negative predictivity was 97.8%. No serum of healthy controls reacted but that of anisakiasis (45.5%), gnathostomiasis (19.2%), clonorchiasis (15.8%), sparganosis (11.1%), and cysticercosis (6.3%) cross-reacted. Immunoblot analysis on TCLA recognized antigenic proteins of 28- and 30-kDa bands in their dominant protein quantity and strong blotting reactivity. The present results indicate that the ELISA using our TCLA antigen is acceptable by the sensitivity and specificity for serodiagnosis of human toxocariasis. ELISA with TCLA is recommended to make differential diagnosis for patients with any sign of organ infiltration and eosinophilia.